1997
DOI: 10.1002/(sici)1099-1050(199703)6:2<161::aid-hec258>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluation of Mental Health Care Interventions. A Review

Abstract: Due to rising costs, the economic aspects of the mental health care sector are receiving increasing attention. This article scrutinizes 91 published studies in the field of mental health care, applying methodological criteria drawn from epidemiology and economics. The purpose of this study is to provide some insight into the quality of economic evaluation in the field of mental health care. The article shows that few good full economic evaluations studies have been undertaken in the domain of mental health car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
10

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 90 publications
(280 reference statements)
1
43
0
10
Order By: Relevance
“…Recent research has shown some advantage of supported employment over traditional trainand-place models (1,2). However, as has been noted by other researchers (3,4), few cost-effectiveness studies of vocational rehabilitation programs have been undertaken.…”
mentioning
confidence: 98%
“…Recent research has shown some advantage of supported employment over traditional trainand-place models (1,2). However, as has been noted by other researchers (3,4), few cost-effectiveness studies of vocational rehabilitation programs have been undertaken.…”
mentioning
confidence: 98%
“…31,51 In contrast, the relative abundance of health economic studies is clear from international databases of abstracts such as the NHS EED, albeit with some concerns that such studies are less prominent within particular disease classifications, such as mental health and paediatrics. 6,82,83 The evidence presented here suggests considerable variation in the development of infrastructure to support and promote the use of economic evidence in policy making between sectors, between countries and between high-and low-and middle-income countries. However, there is a clear and growing appreciation of the need for such evidence, with investment from many parts of the public policy arena in the advancement of methods for the economic evaluation of public sector services and technologies and the commissioning of economic analyses.…”
Section: Resultsmentioning
confidence: 88%
“…For the economic evaluator, the field of mental health constitutes a veritable challenge (21). The fact that truly comparable groups could not be formed, despite a priori matching on variables described in the literature as essential, underscores the difficulty ofconducting evaluative research in psychiatry.…”
Section: Resultsmentioning
confidence: 99%